Tunable crystal structure and proton conductivity of lanthanide nitrilotrismethylphosphonates - Salcedo, Inés R.; Pérez-Colodrero, Rosario Mercedes; Hix, Gary B.; Cabeza-Díaz, Aurelio; Bazaga-García, Montse; Ramírez-Losilla, Enrique; Olivera-Pastor, Pascual (My University, 2018)
Metal phosphonates are multifunctional solids with remarkable stability and proton conducting properties owing to their structure is usually composed of extended hydrogen-bond networks that favor proton transfer pathways [1]. Moreover, these properties can be enhanced by appropriate modification of the synthesis conditions [2, 3]. In this communication, a new family of isostructural 2D layered compounds based on lanthanide nitrilotris-methylphosphonates is reported. These compounds have been isolated at room temperature and have the general formula Ln[N(CH2)3(PO3H2)2(PO3H)(H2O)]SO4·2H2O (Ln= Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er and Yb). The coordination environment of Ln3+ is composed by eight oxygen atoms from three different ligands and two oxygens from bound waters. This connectivity creates positive charged layers connected to sulfate ions through hydrogen-bonds. These compounds show promising proton conductivity with values ranging between 7.6·10-2 and 3.8·10-2 S·cm-1 at 80 °C and 95% RH and low activation energy corresponding to Grotthuss-type proton transfer mechanism. In addition, a structural transformation occurs at T > 70 °C accompanied by a remarkable enhanced conductivity. Studies on the structure-properties relationships will be discussed.
Keywords: Compuestos orgánicos; Metal phosphonates; Coordination polymers; Hybrid materials; Proton conductivity; Crystal structure